EMOSI MARAH DALAM BAHASA MINANGKABAU - Yanti, Yusrita (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2018)
This paper describes a study of emotional expressions of anger in Minangkabau language (BM) because every language has a different vocabulary for basic emotional expressions as well as in BM. From the research done by Yanti (2013a, 2014), she found angry emotions in BM that can be expressed literally and metaphorically. The data of the research were taken from the Max Planck Institute for Evolutionary Anthropology's Padang Field station database, and a number of newspapers using BM. The research used qualitative descriptive method because it describes the result of the study with words not by statistic number. Some theories used in this study refers to the concepts stated by Parrot (2001), Kovecses (2002), Fiehler (2002), Fournier (2009), Yanti (2013, 2013a). The results show (1) variations of vocabularies used to express angry emotions in BM, such as berang, bangih, and marabo, and (2) angry emotions expressed metaphorically, i.e. an analogy of a concept to another concept that has a similarity, such as anger with boiling hot liquid, anger with physical annoyance or pain, for example manggalagak darah, mandidiah darah, marumeh / mamiyuah paruik. Then, the results are useful for the learners who study Minangkabau language as additional information of the Minangkabau language dictionary, especially for angry words as well as inspiring linguists or others to do the further researches about language and emotion.Makalah ini memaparkan tentang kajian bahasa emosi marah dalam bahasa Minangkabau (BM). Setiap bahasa memiliki kosakata yang berbeda untuk ungkapan emosi dasar begitu juga dalam BM. Dari penelitian Yanti (2013a,2014) ditemukan emosi marah dalam BM yang dapat diungkapkan secara harfiah dan secara metaforis. Data penelitian diambil dari database Max Planck Institute for Evolutionary Anthropology’s Padang Field station, dan sejumlah koran yang menggunakan BM. Penelitian bersifat deskriptif kualitatif karena memaparkan hasil kajian dengan kata-kata tidak menggunakan angka statistik. Konsep teoretis yang digunakan diambil dari Parrot (2001), Kovecses (2002), Fiehler (2002), Yanti (2013). Dari hasil kajian ditemukan (1) variasi kosakata emosi marah dalam BM, seperti berang, bangih, dan marabo, (2) emosi marah secara metaforis, yaitu menganalogikan rasa marah dengan sesuatu yang memiliki kesamaan sifat, seperti marah dengan cairan panas yang mendidih, marah dengan sakit fisik, misalnya manggalagak darah, mandidiah darah, marumeh/mamiyuah paruik. Hasil penelitian ini bermanfaat bagi pemelajar BM, sebagai informasi tambahan untuk melengkapi kamus BM, khususnya tentang kata berang ‘marah’ sekaligus sebagai inspirasi bagi ahli bahasa untuk penelitian bahasa dan emosi.